The influence of menstruation and hormonal birth control on the performance of female collegiate lacrosse players - Humphries, H.; Marchelli, G.; Bunn, J. A. (Sports, 2024)
This study compared the mechanical and physiological load placed on Division I female collegiate lacrosse athletes (1) with and without hormone contraceptive (HC) use and (2) with and without menstruation during training and games. Athletes` (20.6 ± 1.5 years, HC users = 9, naturally cycling (NC) athletes = 9) workloads—total distance traveled (TD, m), max speed (km·h-1), accelerations (repetitions), decelerations (repetitions), and high-intensity distance (HID, m)—were measured through VX Sport wearable microtechnology in training sessions (n = 87/athlete) and games (n = 17/athlete). Analyses showed no statistical group differences based on HC use or not, and no differences during menstruation versus non-menstruation for training or games. However, while not statistically different, athletes taking HCs performed worse during menstruation, with a 5.1% decline in decelerations, 3.4% decline in TD and HID, 1.2% decline in max speed, and 1% decline in accelerations. NC athletes did not show this same decline with menses. Given that withdrawal bleeding exacerbates performance reduction of HC users, it may be beneficial for these athletes to consider skipping their withdrawal bleed if it is likely to coincide with a game. Further research needs to be carried out to see if these trends are consistent across other female athletes in other sports.